2014
DOI: 10.1080/1065657x.2014.941515
|View full text |Cite
|
Sign up to set email alerts
|

Pelletized Biochar as a Carrier for AM Fungi in the On-Farm System of Inoculum Production in Compost and Vermiculite Mixtures

Abstract: On farm production of arbuscular mycorrhizal (AM) fungi is suitable for vegetable and horticultural crop production because the inocula may be efficiently mixed into horticultural potting media for plant production in the greenhouse. These inocula are not amenable for use in row crop production because they are not in a form suitable for mechanical application. Experiments were conducted in which light expanded clay aggregates (LECA) and pelletized biochar were used in the media for the on-farm production of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 34 publications
0
8
1
1
Order By: Relevance
“…While many studies demonstrated the ability of biochar amendment to increase the population of microorganisms (Douds et al, 2014;Hua et al, 2011;Yoshizawa et al, 2005;Zhang and Sun, 2014), no significant increase of the number of culturable bacteria was observed in this study. In particular, all the above mentioned studies involve the use of a primary source of nutrients (green waste or sludge) along with biochar addition.…”
Section: Microbial Counts and Respiration Ratecontrasting
confidence: 72%
“…While many studies demonstrated the ability of biochar amendment to increase the population of microorganisms (Douds et al, 2014;Hua et al, 2011;Yoshizawa et al, 2005;Zhang and Sun, 2014), no significant increase of the number of culturable bacteria was observed in this study. In particular, all the above mentioned studies involve the use of a primary source of nutrients (green waste or sludge) along with biochar addition.…”
Section: Microbial Counts and Respiration Ratecontrasting
confidence: 72%
“…The literature provides a great number of studies on different types of biochars used as sorbents for removal of various organic and inorganic contaminants, soil amendments and fertilizers, supplementary materials for composting and anaerobic digestion, additives for remediation of contaminated soil, etc. [10][11][12][13][14]. The most recent applications include using biochar as a potential hydroponic growth substrate [15], a biochar composite membrane or a wood polymer composite [16,17], a green roof substrate [18] or a microbial carrier [19].…”
Section: Introductionmentioning
confidence: 99%
“…Available studies on biochar as a carrier for bacterial strains show positive effects of the biochar on the inoculated microorganisms [22,25,26]. For example, Hale, Luth, Kenney and Crowley [22] used pinewood biochar as an inoculant carrier for a plant growth-promoting rhizobacteria (PGPR) strain (Enterobacter cloacae UW5) in a pot trial and observed an improvement in survival of the bacteria compared with conventional inoculation with a microbial suspension.…”
Section: A C C E P T E Dmentioning
confidence: 99%